2021
DOI: 10.1108/cc-02-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Re-structuring library resources and services in IIT Delhi library: analytical study from users' perspective

Abstract: Purpose This study aims to assess users' satisfaction from the re-structured library resources and services due to technological innovations in the Indian Institute of Technology Delhi library. It also identifies and suggests potential improvement areas. Design/methodology/approach The study adopts a survey research method to collect data from the end-users of the library. Data were collected through a structured questionnaire. In total, 100 copies of questionnaires were distributed to the students, and out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Restructuring the library, according to Xiao (2020) and Raju et al (2018), meets the needs of diverse users by promoting the flow of knowledge and expanding the state-of-the-art services of the 21stcentury academic library. As Kumar and Gupta (2022) study the restructuring of library resources and services at IIT Delhi library and find that user usage and preferences for electronic resources and services are increasing. Several more studies found that WhatsApp and instant messaging usage frequency among university students increased because of their convenience, speed and textual record (Charbonneau and Vardell, 2022;Tsang and Chiu, 2022;Guo et al, 2022;Hurley and Warner, 2022;Dempsey et al, 2022;Sinhababu and Kumar, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Restructuring the library, according to Xiao (2020) and Raju et al (2018), meets the needs of diverse users by promoting the flow of knowledge and expanding the state-of-the-art services of the 21stcentury academic library. As Kumar and Gupta (2022) study the restructuring of library resources and services at IIT Delhi library and find that user usage and preferences for electronic resources and services are increasing. Several more studies found that WhatsApp and instant messaging usage frequency among university students increased because of their convenience, speed and textual record (Charbonneau and Vardell, 2022;Tsang and Chiu, 2022;Guo et al, 2022;Hurley and Warner, 2022;Dempsey et al, 2022;Sinhababu and Kumar, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%